Evaluations on an anthropomorphic vessel from İstanbul Archaeology Museums: The discussion of the ring-shaped idol or pendant and the mother goddess symbolism - Congur, Fatih; Sezer, Okan (Walter De Gruyter Gmbh, 2025)
The anthropomorphic vessel, which entered the inventory of & Idot;stanbul Archaeology Museums as a donation in 2022, has an insightful point with plastic decoration. The vessel, which we believe to be of Yortan origin, is in the shape of a beak spouted jug. Based on its form and production features such as paste, firing, and surface slip, it should be dated to Early Bronze Age (EBA) II. Its plastic decoration shows a composition that has never been seen before in two- and three-dimensional artifacts. This composition allows us to define and model the appearance of the people who lived in this period. The plastic decorations consist of two almond-shaped ears not fully pierced under the mouth rim, one of them with earring, a pendant with beads made by horizontal relief band technique on a place between the neck and the body, and hands-arms stretching from below the handle to the swollen belly. Considering that the majority of anthropomorphic vessels from Western Anatolia and Central-Eastern Europe, dating from Neolithic to EBA, are female, the way the arms are stretched through the squat body and the position of the hands over the body, and also that these ways stretching and bearing are similar to those on female figurines from Central and Western Anatolia dating from the 3rd millennium BC, it indicates that the represented (person) on the vessel is female. In addition, it is possible to make new contributions to the definition, origin, and dating discussion of the ring-shaped idol or pendant and amulet groups in Anatolian archaeology. It has become clear that at least one of the previously unclear uses of the ring-shaped idols or pendants was as a pendant, so that they were worn around the neck. Moreover, the unique composition of plastic decorations, together with the relevant knowledge from written records, indicates that the vessel was probably used for symbolic meanings in rituals. It would not be wrong to suggest that among these symbolic meanings is the one related to the belief in the Mother Goddess, based on the form and/or appearance of the vessel.
Keywords: Early Bronze Age; Western Anatolia; Ring-shaped Idol/Pendant; Mother Goddess; Early Bronze Age; Western Anatolia; Anthropo-morphic Vessel; Ring-shaped Idol/Pendant; Mother Goddess